Interferon-γ and proliferation responses to Salmonella enterica Serotype Typhi proteins in patients with S. Typhi Bacteremia in Dhaka, Bangladesh. - Alaullah Sheikh; Farhana Khanam; Md Abu Sayeed; Taibur Rahman; Marcin Pacek; Yanhui Hu; Andrea Rollins; Md Saruar Bhuiyan; Sean Rollins; Anuj Kalsy; Mohammad Arifuzzaman; Daniel T Leung; et al. (PLoS Neglected Tropical Diseases, 2011)
Salmonella enterica serotype Typhi is a human-restricted intracellular pathogen and the cause of typhoid fever. Cellular immune responses are required to control and clear Salmonella infection. Despite this, there are limited data on cellular immune responses in humans infected with wild type S. Typhi.For this work, we used an automated approach to purify a subset of S. Typhi proteins identified in previous antibody-based immuno-affinity screens and antigens known to be expressed in vivo, including StaF-putative fimbrial protein-STY0202, StbB-fimbrial chaperone-STY0372, CsgF-involved in curli production-STY1177, CsgD- putative regulatory protein-STY1179, OppA-periplasmic oligopeptide binding protein precursor-STY1304, PagC-outer membrane invasion protein-STY1878, and conserved hypothetical protein-STY2195; we also generated and analyzed a crude membrane preparation of S. Typhi (MP). In comparison to samples collected from uninfected Bangladeshi and North American participants, we detected significant interferon-γ responses in PBMCs stimulated with MP, StaF, StbB, CsgF, CsgD, OppA, STY2195, and PagC in patients bacteremic with S. Typhi in Bangladesh. The majority of interferon-γ expressing T cells were CD4 cells, although CD8 responses also occurred. We also assessed cellular proliferation responses in bacteremic patients, and confirmed increased responses in infected individuals to MP, StaF, STY2195, and PagC in convalescent compared to acute phase samples and compared to controls. StaF is a fimbrial protein homologous to E. coli YadK, and contains a Pfam motif thought to be involved in cellular adhesion. PagC is expressed in vivo under the control of the virulence-associated PhoP-regulon required for intra-macrophage survival of Salmonella. STY2195 is a conserved hypothetical protein of unknown function.This is the first analysis of cellular immune responses to purified S. Typhi antigens in patients with typhoid fever. These results indicate that patients generate significant CD4 and CD8 interferon-γ responses ...